The Relationship Between Homeownership and the Utilization of Local Public Health Services Among Rural Migrants in China: A Nationwide Cross-Sectional Study - Wang, Zicheng; Wu, Qiushi; Ming, Juan (Frontiers in Public Health, 2020)
Background: Rural–urban migrants frequently suffer from overrepresented health risks but have poor access to public health services. In China, homeownership status may play a vital role in attaining local welfare. However, the relationship between homeownership and utilization of public health services remains unexplored. This study aims to address the direct linkage between homeownership and utilization of local public health services among rural migrants in China. Methods: The dataset from the 2017 National Migrants Population Dynamic Monitoring Survey (NMPDMS-2017) is applied to explore the direct relationship between homeownership and the utilization of local public health services. The Logit regression is conducted to discuss the associations and to explore the interaction effect. Results: The Logit estimations reveal that homeownership is positively related to the establishment of a health record and the participation in health education. The interaction term of homeownership and household location and the interaction between homeownership and healthcare center location are related to the increased establishment of a health record. However, the interaction of homeownership and household location merely reveals significant correlations with the health education model. Conclusion: Homeownership is positive associated with the utilization of local public health services among rural migrants in China. Furthermore, homeowners living in urban residential communities and within the vicinity of the healthcare center are more likely to access the public health services than those living in other locations.